(untitled) (Acta Scientiarum. Biological Sciences, 2022)
ErpY-like protein (LIC11966) is an antigen from Leptospira spp., which is possibly involved in the infection process and, consequently, can be a promising solution for the development of new diagnostic tests and vaccines. Here, the presence of the erpY-like gene was evaluated in several Leptospira serovars by polymerase chain reaction (PCR), and the ErpY-like recombinant protein was produced and characterized in terms of antigenicity and immunogenicity in vivo. The erpY-like gene was detected by PCR in all Leptospira pathogenic serovars tested (n = 8) and was absent in the saprophytic ones. The rErpY-like protein was recognized by antibodies present in the sera of humans and animals (swine and canine) naturally infected, suggesting ErpY-like expression during natural infection. The rErpY-like protein used to immunize mice with Freund’s adjuvant stimulated a mixed Th1/Th2 response, an important protective immunity against leptospirosis